A Model of Civilization: Imperial Projects, Indigenous Peoples, and “Domiciliation” in Upper Canada, 1784–1844 - Ince, Nathan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
From the 1780s to the 1840s, First Nations leaders and imperial officials in the Great Lakes region frequently made common cause to promote the establishment of Indigenous communities within the territories claimed by the British Empire. Largely made up of refugees from across the newly established international border, these settlements offered Indigenous Peoples the possibility of safety and prosperity, while imperial administrators viewed them as crucial props to British power. Although these projects often invoked the discourse of civilization, the approach they advocated was a far cry from the vision of assimilation that is often understood by “civilization” in today’s historiography. Drawing on the model of the nations domiciliées of the St. Lawrence Valley, these projects could be better understood as following a model of “domiciliation,” defined by military alliance, Indigenous autonomy, and the selective adoption of elements of transatlantic culture. This model, however, was consistently challenged by a discourse of “half-civilization” that by the mid-1840s gave rise to a more totalizing policy of assimilation.